Khat Use Patterns, Associated Features, and Psychological Problems in a Khat-Treatment-Seeking Student Sample of Jimma University, Southwestern Ethiopia - Hassen, Mekdem Tesfamichael; Soboka, Matiwos; Widmann, Marina; Keller, Lucas; Zeller, Anja C.; Büchele, Natascha; Barnewitz, Eva; Yitayih, Yimenu; Schiller, Sabine; Senger, Jael; Adorjan, Kristina; Odenwald, Michael (Frontiers in Public Health, 2021)
Background: Khat (Catha edulis) is a traditionally used substance in African and Arab countries that contains the amphetamine-like alkaloid cathinone. Khat use among Ethiopian students is a growing concern. This study aims to describe khat use, psychological problems, and motivation to change and to determine associated factors of khat use among students from Jimma University seeking psychological assistance. Methods: In a cross-sectional study, a sample of 717 students from Jimma University, southwestern Ethiopia, who seek assistance to reduce khat use were recruited. The study used Amharic and Afaan Oromoo language versions of common psychological instruments and employed them as part of a comprehensive tablet computer-delivered self-report assessment battery, comprising the SRQ-20, the PCL-5, the LEC-5, the AUDIT, and the SOCRATES-khat. In addition, socio-demographic, economic variables, and functioning problems due to severe mental disorders were assessed. The analysis relied on the data of the 575 included participants and used clinical cut-off values to describe this treatment-seeking sample and hierarchical regression models to determine variables associated with khat use. Results: The sample showed high khat use in the past month (M = 31.55 bundles, SD = 28.53, on M = 15.11 days, SD = 8.54); 17.0% showed highly problematic use. The sample was extremely burdened with comorbid psychiatric problems: 21.6% reported functioning problems due to past mental disorders, 60.2% scored above the cut-off for current common mental disorders, 37.9% screened positive for PTSD, and 47.1% reported hazardous alcohol use. Small to medium intercorrelations between variables were detected, and in hierarchical regression models, higher motivation to change khat use was associated with higher use of the substance. Conclusions: This study clearly shows the need to develop research instruments, screening methods, and assistance services for khat-using students at Jimma University. Study participants’ high mental health burden shows the need for targeted intervention programs that go beyond brief interventions for khat use. Furthermore, the study highlights challenges for implementing such services: the barriers to utilization for females and khat users without comorbid mental health problems.